World Intellectual Property Report 2017 : Intangible Capital in Global Value Chains. - Organization, World Intellectual Property (World Intellectual Property Report., 2017)
The World Intellectual Property Report 2017 examines the crucial role of intangibles such as technology, design and branding in international manufacturing. Macroeconomic analysis is complemented by case studies of the global value chains for three products - coffee, photovoltaic energy cells and smartphones - to give an insightful picture of the importance of intellectual property and other intangibles in modern production.